2018
DOI: 10.1177/1687814018766916
|View full text |Cite
|
Sign up to set email alerts
|

Research on the technology of noise reduction in hybrid electric vehicle with composite materials

Abstract: The noise source of hybrid electric vehicle is varied, which makes the frequency band from low-frequency to highfrequency distribution. Using a single material to control the hybrid electric vehicle interior noise to improve the performance of vehicle, noise, vibration, and harshness performance is limited. In this article, the composite noise reduction materials which have the function of damping and acoustic absorption are used to control the vehicle interior noise. First, the noise characteristics of the hy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 11 publications
0
9
0
1
Order By: Relevance
“…The loss factor of the composite beam with the composite elastomer was high in the range of 1–2 kHz. In recent years, the shift to hybrid electric vehicles (HEVs) and electric vehicles (EVs) has been promoted, and it has been reported that the noise in the 1–2 kHz band is higher in HEVs than in automobiles with conventional engines . With the need to address global environmental issues, the electrification of automobiles is an important issue that cannot be avoided, and composite elastomers with high transparency and vibration-damping properties are expected to be applied as materials for next-generation vehicles.…”
Section: Results and Discussionmentioning
confidence: 99%
“…The loss factor of the composite beam with the composite elastomer was high in the range of 1–2 kHz. In recent years, the shift to hybrid electric vehicles (HEVs) and electric vehicles (EVs) has been promoted, and it has been reported that the noise in the 1–2 kHz band is higher in HEVs than in automobiles with conventional engines . With the need to address global environmental issues, the electrification of automobiles is an important issue that cannot be avoided, and composite elastomers with high transparency and vibration-damping properties are expected to be applied as materials for next-generation vehicles.…”
Section: Results and Discussionmentioning
confidence: 99%
“…However, the noise and vibration produced during the HEV operation reduce the comfort of the passengers. They also cause stress, fatigue, and adversely affect the drivers [1,2].…”
Section: Introductionmentioning
confidence: 99%
“…This means that there is a large range of frequencies from, low-frequency to high-frequency distributions. In the paper [ 19 , 20 ], a composite used for the noise reduction with damping and acoustic absorption properties was study for the control of the vehicle’s interior noise. The research showed significant improvements in the noise, vibration, and harshness performance.…”
Section: Introductionmentioning
confidence: 99%